Connections between redlining, food access, hypertension, diabetes, and obesity in Boston - Mehrtash, Farhad (Frontiers in Public Health, 2025)
This paper explores how redlining has disproportionately impacted the Boston neighborhoods of Dorchester, Roxbury, and Mattapan. Initiated in the 1930s, the discriminatory practice of marking these neighborhoods as high-risk for lending has led to significant health inequities today. The paper focuses on how limited access to healthier foods in these areas contributes to a higher prevalence of chronic diseases such as hypertension and obesity, compared to wealthier neighborhoods. Additionally, the paper examines interventions aimed at reducing health disparities by improving affordability and access to nutritious foods. The findings underscore the need for comprehensive policies and interventions with community-based involvement to address food insecurity and health disparities that originated from redlining in Boston.